Cublak-Cublak Suweng: A Structural and Anthropolinguistic Analysis from the Perspective of Cultural Socialization in Early Childhood Education - Yohana Rahajeng Sekarningrum; Doni Dwi Hartanto (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2026)
Cublak-Cublak Suweng is one of the Javanese traditional children's songs that reflects cultural values. The current study aims to study the function of nursery songs, also known as tembang dolanan. This study employed a qualitative ethnographic approach, drawing on anthropological and linguistic analysis. The data in the study were collected through participatory observation, in-depth interviews, and documentation of song lyrics and game recordings. The analysis focused on linguistic aspects, symbols, cultural values, and game practices that involved children's multisensory experiences. The results of the study shown: (1) The perspective of linguistic, the repetitive and rhythmic diction structure in CCS song strengthens the language acquisition enriches the vocabulary; (2) The perspective of anthropology, symbols of movement and lyrics reflect the values of mutual cooperation, compliance with governing norms, and the intergenerational transmission of traditions; and (3) The perspective of learning relevance, practice of singing and playing CCS can be integrated into early childhood education. The latest finding aims to develop cognitive, socio-emotional, and spiritual domains aligned with local culture. The tembang dolanan can be used as a relevant culture-based learning medium in early childhood education. At the same time, tembang dolanan can also help preserve local traditions amid globalization.